The effect of isosorbide-mononitrate on proteinuria in patients with diabetic nephropathy - Demirci, Recep; Akyüz, Okan (Journal of Surgery and Medicine, 2021)
Background/Aim: Diabetic nephropathy (DN) occurs in approximately 40% of patients with Type 1 and Type 2 diabetes mellitus (DM) and is one of the most common causes of end-stage renal disease (ESRD). New treatment strategies are needed to prevent DN. This study aims to investigate the effect of the use of isosorbide-mononitrate (IMN) on diabetic nephropathy. Methods: In this study, patients with type 2 diabetes mellitus were divided into two groups, as those using and not using IMN to evaluate whether IMN reduces proteinuria. Biochemical parameters and proteinuria values were recorded and comparatively analyzed. Results: The urea and creatinine values of patients with type 2 DM who were using IMN were significantly higher and e-GFR values were significantly lower than those of the control group (P=0.049, P=0.001, P=0.013, respectively). However, the proteinuria amounts of Type 2 DM patients using IMN (0.98 g/day [0.52-1.43]) were significantly lower than those who were not (1.61 g/day [1.02-2.69] (P=0.001)). Conclusion: The addition of nitrate to angiotensin-converting enzyme inhibitor (ACEI) or angiotensin II receptor blocker (ARB) in the treatment of patients with DN may be a new alternative for reducing proteinuria.